Offner stretcher for the PEARL laser facility. (September 2017) - Zuev, A.S.; Ginzburg, V.N.; Kochetkov, A.A.; Shaykin, A.A.; Yakovlev, I.V.
Abstract: As part of upgrading the PEARL laser facility, a new, femtosecond Ti : sapphire master oscillator with a centre wavelength of 910 nm and an emission bandwidth of 40.5 nm has been incorporated into its scheme. To produce a new stretcher matched to the compressor of PEARL, we have carried out a comparative analysis of Martinez and Offner stretcher configurations with spherical and parabolic mirrors. The residual dispersion in the stretcher – compressor system has been evaluated using an unconventional approach based on calculation of a zero-dispersion stretcher. In experiments using the Ti : sapphire laser, a new stretcher in the Offner configuration with spherical mirrors and a compressor, we have obtained pulses of 36-fs duration, which is considerably shorter than the current pulse duration in PEARL.